Common occurrence of Cryptosporidium hominis in asymptomatic and symptomatic calves in France. - Romy Razakandrainibe; El Hadji Ibrahima Diawara; Damien Costa; Laetitia Le Goff; Denis Lemeteil; Jean Jacques Ballet; Gilles Gargala; Loïc Favennec (Public Library of Science (PLoS), 2018)
Cryptosporidium spp. infections are the most frequent parasitic cause of diarrhea in humans and cattle. However, asymptomatic cases are less often documented than symptomatic cases or cases with experimentally infected animals. Cryptosporidium (C.) hominis infection accounts for the majority of pediatric cases in several countries, while C. parvum is a major cause of diarrhea in neonatal calves. In cattle Cryptosporidium spp. infection can be caused by C. parvum, C. bovis, C.andersoni and C. ryanae, and recently, reports of cattle cases of C. hominis cryptosporidiosis cases suggest that the presence of C. hominis in calves was previously underestimated.From February to November 2015, Cryptosporidium spp. infected calves were detected in 29/44 randomly included farms from 5 geographic regions of France. C. hominis and C. parvum were found in 12/44 and 26/44 farms, respectively with higher C. hominis prevalence in the western region. In 9 farms, both C. parvum and C. hominis were detected. Eighty-six of 412 (73/342 asymptomatic and 13/70 symptomatic) one to nine-week-old calves shed C. hominis or C. parvum oocysts (15 and 71 calves, respectively), with no mixed infection detected. The predominant C. hominis IbA9G3 genotype was present in all regions, and more frequent in the western region. An incompletely characterized Ib, and the IbA13G3, IbA9G2 and IbA14G2 genotypes were present only in the western region. For C. parvum, the most frequent genotype was IIaA16G3R1 with no geographic clustering. Most C. hominis infected calves were asymptomatic, with some exceptions of IbA9G2 and IbA9G3 isolates, while C. parvum IIaA16G3R1 was associated with symptoms.Present results indicate for the first time that in several geographic regions of France, C. hominis was present in about one fifth of both asymptomatic and symptomatic infected calves, with isolated genotypes likely associated with human infection. Further investigations are aimed at documenting direct or indirect transmissions between livestock and humans.